The role of traditional healers and Primary Health Care in South Africa - Geoffrey Setswe (AOSIS, 1999)
There has been a growing realisation of the importance of traditional medicine all over the world. Opsomming Daar is 'n groeiende bewuswording regoor die wereld van die belangrikheid van tradisionele medisyne. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.